Digital Inheritance: Scope and Challenges - Shalabh Agarwal; Asoke Nath (Mathematics and Computer Science: Research Updates Vol. 3, 2025)
When someone passes away, they may have more than just physical possessions or property. Their trail extends into cyberspace as well. Their being there on social media, investment sites, and other locations on the internet, may have some financial value, present or future. People are living their lives online more and more nowadays. People access internet banking, investments online and communication with family and friends through various social media and other means over the internet. (Jones, S., 2004). In this context, it is becoming more and more important what happens to their digital existence after their death. In the process of digital inheritance, digital media is handed over to the beneficiaries in the form of rights and digital assets understanding the rights that exist with the beneficiaries after a person’s death. As the digital inheritance concept is quite fresh, substantial legal systems are yet to be established to deal with matters after their death. It is for that reason the websites govern the act of the users. It is clear that a comprehensive legal arrangement is necessary to address this important issue of digital inheritance and hopefully, this will be dealt with by the various Governments across the world in due course. This paper explains the concept of Digital Inheritance and explores the various options social media services provide for managing a deceased user’s data (Bohanna, 2016). An effort is also made to suggest that Digital Will may be a choice to address this problem. The study concluded that at an individual level, one should meticulously plan the destiny of the digital content after his or her demise. There may be some important digital content very relevant, required and of sentimental value to the next to-kin and, family and friends.